The Effect of STEM Learning in Building Creative Dispositions and Creative Thinking Skills of Junior High School Students - Sawu, Maria Rosalinda Febrianti; Sukarso, AA; Lestari, Tri Ayu; Handayani, Baiq Sri (Postgraduate, University of Mataram, 2023)
Education in the 21st century, students need to be equipped with life skills, one of which is creative thinking skills. Creative thinking skills cannot be separated from creative dispositions or what can be called creative character and habits. This study aims to determine the effect of using the STEM learning approach in building creative dispositions and creative thinking skills of junior high school students. The research design used was Nonequivalent control group design and the sampling technique was random sampling method. The independent variables of the research are the STEM learning approach (experimental class) and the scientific learning approach with verification practicum methods (control class). The dependent variable of the research is creative disposition and students' creative thinking skills. Data on students' creative dispositions were obtained from a creative disposition questionnaire while data on students' creative thinking skills were obtained from tests of creative thinking skills which were compiled based on indicators of creative thinking skills. Hypothesis testing in this study used the ANACOVA test. The results of the research on students' creative dispositions obtained the value of Sig. (Î±) = 0.000 <0.05 while creative thinking skills obtained Sig. (Î±) = 0.005 < 0.05. The results of the study showed that students who were taught using the STEM learning approach were better than students who were taught with a scientific learning approach using the verification practicum method.